Verification and evaluation of computer and communication systems : 12th International Conference, VECoS 2018, Grenoble, France, September 26-28, 2018, Proceedings /: 12th International Conference, VECoS 2018, Grenoble, France, September 26-28, 2018, Proceedings. (2018) - Unknown
No abstract available